Evaluación de la presencia de abscesos en el cuello y tren posterior en las canales bovinas de un Frigorífico ubicado en el Departamento de Caldas, Colombia (2013)
The study was of a descriptive type, and it searched to evaluate the abscesses presented in bovine carcasses at the neck level (longissimus dorsi muscle and rhomboidal muscle) and the hind leg (gluteal muscles and bicep femoris muscle), considering the following variables: number, location, size and weight of the abscesses, and the degree of compromise of the lesion in the carcass section, and the number and weight of the economical losses, from a sample of 2902 animals, processed in an abattoir located in the province of Caldas, coming from 69 farms, of 22 cities in 8 provinces during a period of 30 days. From the four commercial carcass sections, there were 1971 abscesses, with 27% of animals coming from the province of Antioquia, 23.03% from Santander and 20.45% from Cundinamarca, showing that the most affected cuts were located in the neck with a total of 1051 (53.32%) abscesses, followed by the hind leg with 578 abscesses (29.33%). In relation to the size, amplitude and deepness the results were similar between the different sections of the carcass, showing that lesions with measures of 3 to 6 cm were related to a degree of compromise level 2, corresponding to a 76%. The confiscated total amount was 317.5 kg, being the neck section the greatest amount (186.5 kg), with an average of 180 g/abscess. The economical losses in the period reached $4.360.812. It was deducted that the lesions are a consequence of inadequate management practices, sanitary control and innocuity, possibly caused by practice of usage and application of veterinary drugs.